In Search of Lost Weather: Temporal Reflexivity and Ecological Awareness in Participatory Performance - Jamie Harper (Ambiances)
This article argues that temporal reflexivity in participatory performance practices can support the agency of participants by inviting them to compare past and future imaginings to inform creative action in the present. In contrast with contemporary forms of immersive performance which valorise the immediacy of presence, the article argues that immersive atmospheres that focus perception on the immanent moment of now can restrict creative volition. This proposition is developed with reference to Spinoza’s theory of affects which suggests that being driven by the affects of the present can render the human body passive. An alternative aesthetics of temporal reflexivity is presented through discussion of participatory performance projects using live action role-play drama that were designed and facilitated by the author during 2017-2018. Insights drawn from these projects suggest that a depth perspective on time can heighten participants’ awareness of relational connections within the atmospheric conditions of their play and expand their creative capacities to make their own atmospheres. The latter part of the article draws on Gregory Bateson’s theories of ecology to conclude that temporal reflexivity can enhance ecological awareness, enabling individuals to undertake volitional action to purposefully shape the atmospheres, or ecologies, that they play, and live, within.